The role of governmental policy in game between traditional fuel and new energy vehicles. (July 2022) - Liao, Haolan; Peng, Sainan; Li, Lu; Zhu, Yi
Abstract: New energy vehicle (NEV) effectively contributes to the sustainable direction of the automobile industry, and it has been raised to the national strategic level. Our study establishes a quantitative model on the competition between firms producing traditional fuel vehicle (TFV) and those manufacturing NEVs, based on the game theory, in which both sides can adopt a cooperative or a non-cooperative strategy. Validated by an empirical analysis and other examples, the results demonstrate that, in a stock market, though the competition of market share between TFV and NEV firms is a zero-sum game, there still exists the possibility wherein firms can cooperate to achieve a win–win situation in terms of the profit. Importantly, by modeling the decision-making processes under governmental policies, we analyze the impacts of different regulation intensities on the promotion effect of NEVs. Grounded with data collected from the automobile manufacturing industry, our model illustrates that although the government's subsidy has certain promoting effect on NEV marketing, it does not improve the profitability of the firms no matter from supply-side subsidy or consumer-side subsidy. With the gradual withdrawal of financial subsidies, dual credit policy will significantly contribute toward balancing the competition between TFVs and NEVs. Thus, this analysis is expected to provide a theoretical foundation that administrators can refer to when employing effective policy instruments to balance the competition between TFVs and NEVs, thereby steering the NEV industry toward a sustainable direction. Highlights: Non-zero-sum game between traditional fuel and new energy vehicles was conducted. Strategy between the firms for overall profit maximization was derived. The role of government policies in the game process was analyzed quantitatively. Grounded with the data of China's automobile market under stagnant growth sales. Provide theoretical foundation for the scientific decision-making on the policy proposal.